Kontrol Pengereman Sepeda Listrik Berbasis Internet of Things (IoT) dengan Monitoring GPS - Maydia Anggraeni, Putri; Sulistiyowati, Indah; Wisaksono, Arief (JiTEKH, 2022)
Motor vehicles dominate the occurrence of accidents on the highway although there are several factors that cause it, among others, due to mechanical factors and human factors. This electric bicycle is still being developed with features that can improve driving safety which will later have a function to avoid collisions with objects in front of it. By using an ultrasonic sensor as a distance detector and NodeMCU ESP8266 as a microcontroller and with a GPS sensor that displays a map display in the blynk application, this system is expected to be able to create security for motorists so as to reduce the risk of accidents with vehicles or objects in front and at the same time can monitor vehicle position via smartphone. In this study, which will be implemented on an electric bicycle, braking success is obtained without hitting the object in front of it with an average speed of 10-15 km/hour and a maximum distance of 6m from the object and stopping 1m behind the object with 100% accuracy. Braking works from a distance of 3m to the object in front of it and will stop slowly according to the variables at a speed of 3m stop slowly 95o, 2m stop slowly 45o and 1m will stop slowly until it stops, and get slow braking when this automatic brake works